PENGARUH PRODUK BANK SYARIAH TERHADAP MINAT MENABUNG DENGAN PERSEPSI MASYARAKAT SEBAGAI VARIABEL MODERATING DI POLEWALI MANDAR - Muh.Irwan.T (Universitas Islam Negeri Mataram, 2026)
This study aims to examine the impact of Sharia banking products specifically within the Polewali City district on the public's interest in saving, using public perception as a moderating variable. A descriptive quantitative research method was employed, with a population consisting of Bank Syariah Indonesia (BSI) customers in the Polewali Mandar district. The sample comprised 100 respondents individuals conducting transactions at Sharia commercial banks selected using the quota sampling technique. Data analysis was conducted using Moderating Regression Analysis (MRA). The findings indicate that Sharia banking products offered by these financial institutions in the Polewali district have an impact on the community, demonstrating that the products (specifically savings accounts) provide tangible benefits to customers and the public. Furthermore, public perception serves as a moderating variable, as Sharia commercial banks are able to educate the public that their products are free from riba (usury).